Chemical characterisation and biological activity of leaf essential oils obtained from Pistacia terebinthus growing wild in Tunisia and Sardinia Island. Issue 22 (17th November 2017) - Piras, Alessandra; Marzouki, Hanen; Maxia, Andrea; Marengo, Arianna; Porcedda, Silvia; Falconieri, Danilo; Gonçalves, Maria José; Cavaleiro, Carlos; Salgueiro, Ligia
Abstract: In the present work the chemical compositions, measured by GC and GC-MS, of the essential oils obtained by hydrodistillation from leaves of Pistacia terebinthus collected in Bizerte (Tunisia) and Baunei (Italy) are reported. Both essential oils possessed high content of monoterpene hydrocarbons (86.3% and 90.9%, respectively), being α-pinene (62.4 vs . 35.0)%, camphene (3.0 vs . 2.4)%, β-pinene (12.1 vs . 4.5)%, terpinolene (1.7 vs . 35.2)% and β-phellandrene (3.8 vs . 4.5)% the main components. The Tunisian essential oil exhibited higher antifungal activity than the Italian one. Cryptococcus neoformans and the majority of dermatophyte strains showed more sensitivity to the Tunisian oil, when compared to Candida strains, in particular Trichophyton rubrum, Microsporum canis and Epidermophyton floccosum, with MIC and MLC values in the range (0.16–0.32) μL/mL. The results obtained support the use of the oil from Tunisia for the treatment of dermatophytosis. Abstract :